Benchmarking Physical Therapy Practice Strategies for Children with Down Syndrome: A Mini Review - Qurba Kiran; Asima Irshad; Arooj Shahzad; Saleh Shah; Rubab Naqvi (Pakistan Armed Forces Medical Journal, 2026)
The most prevalent chromosomal anomaly is Down syndrome, which affects approximately 0.1% of live births globally. Numerous musculoskeletal consequences, such as bone abnormalities, ligamentous laxity, muscle weakness, and hypermobility are linked to Down syndrome. The role of a physiotherapist in rehabilitation of Down syndrome children is contingent upon their developmental stages and typically involves promoting physical exercise. The purpose of this study is to compare and assess the efficacy of various physical therapy methods in individuals with Down syndrome, as well as to assess the effectiveness of physical therapy in this population. PubMed and Google Scholar were explored by using predefined search terms related to physical therapy interventions and Down syndrome for full text of research articles published in English language in the last 15 years. This narrative review provides an overview of the many physical treatment techniques emphasizing their advantages, limitations, and areas in need of more investigation. The significance of specialized physical therapy interventions for children with Down syndrome is highlighted by this review's findings. Although a number of strategies have demonstrated promise in enhancing motor function and skills according to age, functional abilities and comorbidities. Physically development and functionally independence can be achieved in children with Down syndrome by combining evidence-based physical therapy interventions with multidisciplinary approach. Keywords: Down syndrome, Physiotherapy, Strength, Exercise, Resistance training, Neuromuscular stimulation